2017
DOI: 10.1111/jbi.13103
|View full text |Cite
|
Sign up to set email alerts
|

Community level niche overlap and broad scale biogeographic patterns of bee communities are driven by phylogenetic history

Abstract: Aim Because the ecological similarity between species is expected to increase with relatedness and that speciation is a local process, phylogeny may provide a common measure for the influence of ecological and biogeographic processes on community assembly. We tested if similarities in floral visitation patterns within communities and the phylogenetic beta‐diversity among communities were related to the position of bees within the bee phylogeny. Location Global. Methods We combined a genus level phylogeny with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Based on the current understanding of the biogeographic histories of the 27 crops we sampled, more bee genera were supported in the Neotropics, Indomalaya and Afrotropics by native crops compared to exotic crops. Since closely related bees tend to visit closely related plants [49], native crop assemblages might support more bee genera if they are more taxonomically diverse, but this did not appear to explain our results (see electronic supplementary material). Thus, agricultural landscapes dominated by native crops are expected to support greater bee genus diversity in the predominantly tropical biogeographic realms.…”
Section: Discussionmentioning
confidence: 87%
“…Based on the current understanding of the biogeographic histories of the 27 crops we sampled, more bee genera were supported in the Neotropics, Indomalaya and Afrotropics by native crops compared to exotic crops. Since closely related bees tend to visit closely related plants [49], native crop assemblages might support more bee genera if they are more taxonomically diverse, but this did not appear to explain our results (see electronic supplementary material). Thus, agricultural landscapes dominated by native crops are expected to support greater bee genus diversity in the predominantly tropical biogeographic realms.…”
Section: Discussionmentioning
confidence: 87%
“…Calosphace. We have found no evidence to suggest the bee faunas are strikingly functionally different between the NW and OW; indeed, the bee families Andrenidae, Apidae, Colletidae, Halictidae, and Megachilidae involved in Salvia pollination are common across the NW and OW (Danforth et al 2013;Hedtke et al 2013;Sydenham et al 2017). The only family of bees missing in the NW is the small-sized Melittidae, and there are only a few observations of these visiting OW Salvia (Özbek 2014).…”
Section: Do Switches In Pollinator Impose Long-term Evolutionary Consmentioning
confidence: 80%
“…2013; Sydenham et al. 2017). The only family of bees missing in the NW is the small‐sized Melittidae, and there are only a few observations of these visiting OW Salvia (Özbek 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Pollination success is related to pollinator species occurrence and availability 16 , but it also depends on the biological community assembly 17,[20][21][22] and on the relationship between flower traits (e.g., size and morphology) and the body size of its visitors 23 . Castilla et al 24 showed that pollinator body size contributes to plant seed viability but is apparently not related to long-distance genetic flow.…”
Section: Background and Summarymentioning
confidence: 99%